The Waiver of the Hadd Punishment for Defamation through the Forgiveness of the Defamed Person between Islamic Law and Positive Iraqi Law (Islamic Sciences Journal, 2026)
This study examines the waiver of the hadd punishment for defamation (qadhf) through the forgiveness of the defamed person, an issue that has generated juristic and legal disagreement regarding the nature of the hadd and the effect of the victim’s pardon on the lapse of punishment. The importance of the study stems from divergent juristic views on whether the hadd of qadhf constitutes a right of God, a right of the individual, or a shared right combining both. The study concludes that juristic disagreement over entitlement to the hadd of qadhf has directly influenced rulings on the effect of forgiveness on the punishment. It also finds that Iraqi law gives precedence to the victim’s interest over the public interest. Accordingly, the study recommends reconsidering certain related legal provisions to achieve a balanced approach that protects personal honor while respecting the will of the victim.
Keywords: Hadd of Defamation (Qadhf), Victim’s Forgiveness, Right of God, Right of the Individual, Islamic Jurisprudence